Trading Offshore: Evidence on Banks' Tax Avoidance - Dominika Langenmayr; Franz Reiter (Center for Economic Studies and ifo Institute (CESifo), 2017)
Little is known about how banks shift profits to low-tax countries. Because of their specific business model, banks use profit shifting channels different from those of other firms. We propose a novel and bank-specific method of profit shifting: the strategic relocation of proprietary trading to low-tax jurisdictions. Using regulatory data from the German central bank, we show that a one percentage point lower corporate tax rate increases banks' fixed-income trading assets by 4.0% and trading derivatives by 9.0%. This increase does not arise from a relocation of real activities (i.e. traders); instead, it stems from the relocation of book profits.
Keywords: H25; G21; F21; 330; profit shifting; multinational banks; corporate taxation; proprietary trading